Method for tuning photogenerated charge migration path of COFs (Covalent Organic Frameworks) by transition metal

By coordinating transition metal ions on the COFs skeleton and building a three-phase interface of COF/M/Pt, the problem of low photogenerating charge recombination efficiency in COFs photocatalysts is solved, efficient photocatalytic hydrogen evolution is achieved and cost-reduced, which is suitable for large-scale Production.

CN119186639APending Publication Date: 2024-12-27QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411283156.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The problem of rapid photogenerating charge recombination in existing COFs photocatalytic hydrogen evolution process leads to low efficiency, and the traditional methods are costly and unsuitable for large-scale production.

Method used

By coordinating transition metal ions on the COFs skeleton and building a three-phase interface of COF/M/Pt using photodeposition strategies, transition metal ions space Pt and COFs to prevent electron reflux, realizing directed charge transfer and preventing recombination.

Benefits of technology

The photocatalytic hydrogen evolution efficiency is improved, the load of precious metal Pt is reduced, and it is suitable for large-scale production, and the hydrogen production yield and catalytic stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005042292540000011
    Figure HDA0005042292540000011
  • Figure HDA0005042292540000012
    Figure HDA0005042292540000012
  • Figure HDA0005042292540000021
    Figure HDA0005042292540000021
Patent Text Reader

Abstract

The invention relates to a method for tuning a photogenerated charge migration path of COFs (Covalent Organic Frameworks) by transition metal, which is characterized in that transition metal ions are coordinated on a COFs framework, the coordination amount of the transition metal ions is controlled, and the transition metal ions coordinated on the COFs framework are successfully subjected to in-situ photodeposition by utilizing a photodeposition strategy according to the charge migration and transfer principle, so that the COFs photogenerated charge migration path is tuned. The transition metal is accurately constructed between the COFs and the cocatalyst Pt, the Pt and the COFs are separated through the transition metal, the effect of guiding electron transfer is achieved, backflow of electrons from Pt to the COFs is blocked or cut off, and therefore the method for guiding COFs photo-induced electron directional transfer and preventing backflow compounding of the COFs photo-induced electrons through the transition metal is developed. The constructed composite material is used as a photocatalyst to be used for light-driven hydrogen production, complex COFs monomer design can be effectively avoided, the loading capacity of precious metal Pt is reduced, and the composite material is suitable for practical application of COFs photocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for tuning the COFs photogenerated charge migration path by transition metals, and belongs to the field of porous organic materials and photocatalysis. Background Art

[0002] Energy crisis and environmental pollution have become the most difficult global problems. Converting solar energy into chemical fuels through photocatalytic hydrogen production has developed into a potential and effective technology for obtaining new energy. Covalent organic framework materials (COFs) are highly crystalline porous organic polymer materials connected by organic monomers through covalent bonds. They have the advantages of low density, large specific surface area, high porosity, and highly adjustable chemical structure. They have the properties of n-type organic semiconductors and have attracted widespread attention as an excellent photocatalyst. However, the photocatalytic efficiency of single-component COFs is still low, partly due to the rapid recombination of photogenerated charges. With the government's requirements for low energy consumption and low pollution, and the gradual increase in people's environmental awareness, the development of green and environmentally friendly COFs solar photocatalytic hydrogen evolution technology to further meet the practical application of COFs materials has become an urgent problem to be solved in the field of COFs materials. COFs with various structures have been used in photocatalytic hydrogen evolution research. However, at present, the photocatalytic hydrogen evolution performance can only be improved by changing the COFs skeleton structure. The organic synthesis process is complex and the cost is greatly increased. Therefore, it is urgent and of great significance to develop a simple, low-cost method to improve the photocatalytic hydrogen evolution performance of COFs suitable for large-scale production.

[0003] Transition metals have the characteristics of low cost and high conductivity, and their ionic state exhibits electron-deficient characteristics, which can improve the utilization efficiency of photogenerated charges. The research on various transition metal ion-doped inorganic photocatalysts has well demonstrated the above point of view, but transition metals are rarely used in COFs photocatalytic research. Traditional COFs generally use photodeposition to load Pt nanoparticles as co-catalysts to accelerate the rate of hydrogen evolution reaction, but this method easily causes the photoelectrons that migrate to Pt to recombine with the holes remaining on COFs.

[0004] Therefore, developing efficient strategies for directional charge transfer and preventing electron-hole recombination has become an urgent problem to be solved in the field of COFs photocatalytic materials. In the field of COFs photocatalytic hydrogen evolution, there are currently no reports on solving this problem. Summary of the invention

[0005] In view of the shortcomings of the prior art, especially the problem of countercurrent recombination of photoelectrons between COFs and Pt, the present invention provides a method for tuning the migration path of photogenerated charges in COFs using transition metals.

[0006] The present invention utilizes the advantages of high crystallinity, highly adjustable pore size and pore environment of COFs, coordinates transition metal ions on the COFs skeleton, controls the coordination amount, and uses a photodeposition strategy based on the principle of charge migration and transfer to successfully perform in-situ photodeposition of the transition metal ions coordinated on the COFs skeleton. The present invention accurately constructs the transition metal between COFs and the co-catalyst Pt, and separates Pt and COFs through the transition metal, which not only guides the electron transfer, but also blocks or cuts off the electron backflow from Pt to COFs, thereby developing a method for guiding the directional transfer of photogenerated electrons of COFs by using transition metals and preventing the backflow and recombination thereof, and using the constructed composite material as a photocatalyst for light-driven hydrogen production, which can effectively avoid the cumbersome COFs monomer design and reduce the load of the precious metal Pt, and is suitable for the practical application of COFs photocatalysis.

[0007] The present invention is achieved through the following technical solutions:

[0008] A method for tuning the migration path of photogenerated charges in COFs by transition metals comprises the following steps:

[0009] 1) Coordination of transition metal ions

[0010] The COFs photocatalyst is dispersed in an aqueous solution of transition metal ions, ultrasonically dispersed to make it uniformly mixed, and then stirred at room temperature for coordination adsorption. After the reaction is completed, the product is washed and purified, and the obtained solid is dried to obtain COFs coordinated with metal ions;

[0011] 2) In situ photodeposition of transition metal ions

[0012] The metal ion coordinated COFs are added to an ascorbic acid aqueous solution for dispersion, the air is exhausted with an inert atmosphere, the air is sealed, and the air is placed under visible light for in-situ photoreaction, and the COF-M is obtained after filtration and drying;

[0013] 3) Construction of COF / M / Pt three-phase interface

[0014] The prepared COF-M and H 2 The PtCl6 aqueous solution is co-dispersed in the ascorbic acid aqueous solution, exhausted with an inert atmosphere, sealed, and placed under visible light for photoreaction. The obtained sample is filtered, rinsed with a large amount of deionized water, and dried to obtain a COF / M / Pt structured composite material Pt@COF-M, where M is a transition metal.

[0015] Preferably according to the present invention, in step 1), the concentration of the transition metal ion aqueous solution is 200-300 mM.

[0016] Further preferably, in step 1), the concentration of the transition metal ion aqueous solution is 260-280 mM.

[0017] According to the preferred embodiment of the present invention, in step 1), the transition metal ion is RhCl 3 HAuCl 4 、RuCl 3 AgNO 3 , CuCl 2 ,NiCl 2 or CoCl 3 supply.

[0018] Further preferably, in step 1), the transition metal ion is RhCl 3 HAuCl 4 or RuCl 3 supply.

[0019] Preferably according to the present invention, in step 1), the mass volume ratio of the COFs photocatalyst to the transition metal ion aqueous solution is (8-15):(4-10), unit, mg / uL.

[0020] Preferably, according to the present invention, in step 1), the stirring time at room temperature is 1-6 hours, the product is washed and purified by washing, filtering and purifying with deionized water, and the drying temperature is 50-100°C.

[0021] Preferably according to the present invention, in step 2), the concentration of the ascorbic acid aqueous solution is 0.001-1M.

[0022] Preferably according to the present invention, in step 2), the mass volume ratio of COFs coordinated by metal ions to the ascorbic acid aqueous solution is (8-15):(80-120), in units of mg / mL.

[0023] Preferably according to the present invention, in step 2), the inert atmosphere is Ar, and the inert atmosphere treatment time is 10 min-2 h.

[0024] Preferably according to the present invention, in step 2), the in situ photoreaction time is 30 min-2 h.

[0025] Preferably according to the present invention, in step 3), the concentration of the chloroplatinic acid aqueous solution is 10-100 mM.

[0026] According to the preferred embodiment of the present invention, in step 3), the amount of COF-M added is 2 H in PtCl6 aqueous solution 2 PtCl 6 The mass ratio is 10:(0.01-0.5).

[0027] Preferably according to the present invention, in step 3), the concentration of the ascorbic acid aqueous solution is 0.001-1M.

[0028] Preferably according to the present invention, in step 3), the mass volume ratio of the added amount of COF-M to the ascorbic acid aqueous solution is (8-15):(80-120), in mg / mL.

[0029] Preferably according to the present invention, in step 3), the inert atmosphere is Ar, and the inert atmosphere treatment time is 30 min-2 h.

[0030] Preferably according to the present invention, in step 3), the light reaction time is 30 min-2 h, and the drying temperature is 50-100°C.

[0031] A COFs / transition metal / Pt nanoparticle composite photocatalyst is prepared by the method.

[0032] Application of COFs / transition metal / Pt nanoparticle composite photocatalysts for light-driven hydrogen production.

[0033] According to the preferred embodiment of the present invention, the specific application method is as follows:

[0034] Under light irradiation, ascorbic acid is used as a sacrificial agent and a COFs / transition metal / Pt nanoparticle composite photocatalyst is used as a catalyst to carry out light-driven hydrogen production. The concentration of the ascorbic acid sacrificial agent is 0.1-5 mol / L, and the mass volume ratio of the catalyst to ascorbic acid is: (5-15): (50-200), in mg / mL.

[0035] Preferably according to the present invention, the concentration of the ascorbic acid sacrificial agent is 0.5-2 mol / L.

[0036] The COFs / transition metal / Pt nanoparticle composite photocatalyst obtained by the present invention has good photocatalytic performance. The loading amount of the surface-modified Pt nanoparticles is 0.1-5%wt of the COFs mass, and the three-phase interface of COFs / M / Pt nanoparticles is perfectly constructed. The transition metal separates Pt from COFs, plays a role in guiding electron transfer and preventing electron backflow.

[0037] The technical features and advantages of the present invention are as follows:

[0038] 1. The present invention takes advantage of the high crystallinity and highly adjustable chemical structure of COFs, coordinates transition metal ions at the active sites of the COFs skeleton, controls the loading amount of the transition metal ions, and uses a photodeposition strategy based on the principle of charge migration and transfer to successfully perform in-situ photodeposition of the transition metal ions coordinated on the COFs skeleton. The present invention accurately constructs the transition metal between COFs and the co-catalyst Pt, and separates Pt and COFs through the transition metal, which not only guides the electron transfer, but also blocks or cuts off the electron backflow from Pt to COFs, thereby developing a method for transition metals to guide the directional transfer of COFs photogenerated electrons and prevent their backflow and recombination. The constructed composite material is used as a photocatalyst for light-driven hydrogen production, which can not only effectively avoid the cumbersome COFs monomer design and reduce the loading amount of the precious metal Pt, but also is suitable for the practical application of COFs photocatalysis, and greatly improves the hydrogen production yield.

[0039] 2. The photocatalytic activity test shows that the COF / transition metal / Pt nanoparticle composite material of the present invention has a stable hydrogen generation rate and a stable cyclic catalytic activity.

[0040] 3. The large specific surface area and regular and adjustable chemical structure are conducive to the coordination and in-situ photodeposition of transition metal ions, as well as the efficient utilization of catalytic active sites and the mass transfer of reactants and products during the reaction. The electron guiding effect of the transition metal ions of the present invention improves the transmission efficiency of photogenerated electrons, not only improves the efficiency of photocatalytic hydrogen evolution, but also reduces the use of precious metal Pt, successfully reducing costs. In addition, due to the electron guiding effect of the transition metal ions, Pt nanoparticles are confined in the COFs pores, so that Pt is almost not leaked, thereby showing excellent photocatalytic hydrogen evolution stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 XRD of 0.25wt% Pt@TpBpy-M prepared by coordination with different metal ions;

[0042] Figure 2 This is a schematic diagram of the construction principle of the COF / M / Pt three-phase interface constructed using TpBpy as a raw material in the present invention;

[0043] Figure 3 TEM and XPS of the 0.25wt% Pt@TpBpy-Rh composite structure prepared in Example 1; a is TEM, bd is TEM;

[0044] Figure 4 The photocatalytic hydrogen evolution performance and stability test of the composite materials prepared in different embodiments and comparative examples; a is different concentrations of Rh 3+The photocatalytic hydrogen evolution performance of the composite material prepared from the aqueous solution, that is, the photocatalytic hydrogen evolution performance of the materials prepared in Example 1 and Comparative Examples 1-2, b is the photocatalytic hydrogen evolution performance of 0.25wt% Pt@TpBpy-M prepared by coordination of different metal ions, c is the apparent quantum efficiency of 0.25wt% Pt@TpBpy-Rh in Example 1, and d is the cycle performance of 0.25wt% Pt@TpBpy-Rh in Example 1.

[0045] Figure 5 The photocurrent and fluorescence lifetime of 0.25wt% Pt@TpBpy-Rh prepared in Example 1, a is the photocurrent, and b is the fluorescence lifetime. DETAILED DESCRIPTION

[0046] Unless otherwise specified in the context of this application, the technical terms and abbreviations used in this application have the conventional meanings known to those skilled in the art; unless otherwise specified, the raw material compounds used in the following examples are commercially available.

[0047] According to the present invention, the material preparation, characterization and testing of various properties are described in detail below. On the contrary, the following examples are only used to further explain and illustrate the present invention, and should not be considered to limit the scope of the present invention, which will only be limited by the claims.

[0048] Conventional photodeposition of Pt nanoparticles is an existing technology.

[0049] The TpBpy-COFs photocatalyst used in the embodiment was prepared specifically by the following method:

[0050] Synthesis of TpBpy-COFs: 2,4,6-trihydroxybenzene-1,3,5-tricarbaldehyde (Tp, 42 mg) and 5,5'-diamino-2,2'-bipyridine (Bpy, 55.8 mg) were added to a Shrek tube, followed by 1 mL of o-dichlorobenzene, 3 mL of N'N-dimethylacetamide, and 0.4 mL of aqueous acetic acid (6 M). The tube was freeze-evacuated at 77 K and the air was exhausted, then sealed, and the tube was transferred to an oil bath and heated at 120 ° C for 3 days to produce a red solid, which was separated by filtration and washed with tetrahydrofuran and methanol in a Soxhlet extractor for 24 hours. TpBpy-COFs were then activated by vacuum drying at 80 ° C for 12 hours (yield 85%). The chemical structure of TpBpy-COFs can be found in Figure 2 .

[0051] Example 1

[0052] The method of transition metal tuning the migration path of photogenerated charges in COFs is as follows:

[0053] 1) Coordination of transition metal ions

[0054] Disperse 10 mg of TpBpy in 5.5 uL of 0.275 umol Rh 3+ In aqueous solution, ultrasonic dispersion is performed to make it uniformly mixed, and then stirring is performed at room temperature for coordination adsorption. After the reaction is completed, the product is washed and purified, and the obtained solid is dried to obtain COFs coordinated by metal ions;

[0055] 2) In situ photodeposition of transition metal ions

[0056] 10 mg of COFs coordinated by metal ions were added to 100 mL of 0.1 M ascorbic acid aqueous solution for dispersion, the air was evacuated with Ar gas, the system was sealed, and placed under visible light for in-situ photoreaction. The obtained sample was filtered, rinsed with a large amount of deionized water, and dried to obtain TpBpy-Rh;

[0057] 3) Construction of COF / M / Pt three-phase interface

[0058] 5.5uL containing 0.025mg of Pt 4+ H 2 PtCl6 aqueous solution and 10 mg of TpBpy-Rh were co-dispersed in 100 mL of 0.1 M ascorbic acid aqueous solution. The air was evacuated with Ar gas and the system was sealed and placed under visible light for photoreaction. The obtained sample was filtered, rinsed with a large amount of deionized water, and dried to obtain 0.25 wt% Pt@TpBpy-Rh, denoted as Pt@TpBpy-Rh. The prepared 0.25 wt% Pt@TpBpy-Rh had a COF / Rh / Pt three-phase interface structure, as shown in FIG. Figure 3 shown.

[0059] Example 2

[0060] The method of using transition metal to tune the migration path of photogenerated charges in COFs described in Example 1 is different in that:

[0061] In step 3), 5.5 uL containing 0.05 mg of Pt 4+ H 2 The PtCl6 aqueous solution and 10 mg of TpBpy-Rh were co-dispersed in 100 mL of 0.1 M ascorbic acid aqueous solution. The rest was carried out as in Example 1 to obtain 0.5 wt% Pt@TpBpy-Rh, recorded as 0.5% Pt@TpBpy-Rh.

[0062] Example 3

[0063] The method of using transition metal to tune the migration path of photogenerated charges in COFs described in Example 1 is different in that:

[0064] In step 1), 0.275 umol of CoCl 3 Aqueous solution replaces Rh 3+ The aqueous solution was prepared as in Example 1 to obtain 0.25 wt% Pt@TpBpy-Co, which was recorded as Pt@TpBpy-Co.

[0065] Example 4

[0066] The method of using transition metal to tune the migration path of photogenerated charges in COFs described in Example 1 is different in that:

[0067] In step 1), 0.275 umol of RuCl 3 Aqueous solution replaces Rh 3+ The aqueous solution was prepared as in Example 1 to obtain 0.25 wt% Pt@TpBpy-Ru, which was recorded as Pt@TpBpy-Ru.

[0068] Example 5

[0069] The method of using transition metal to tune the migration path of photogenerated charges in COFs described in Example 1 is different in that:

[0070] In step 1), 0.275 umol of AgNO 3 Aqueous solution replaces Rh 3+ The aqueous solution was prepared as in Example 1 to obtain 0.25 wt % Pt@TpBpy-Ag, denoted as Pt@TpBpy-Ag.

[0071] Example 6

[0072] The method of using transition metal to tune the migration path of photogenerated charges in COFs described in Example 1 is different in that:

[0073] In step 1), 0.275 umol of CuCl 2 Aqueous solution replaces Rh 3+ aqueous solution, and the rest was carried out as in Example 1 to obtain 0.25wt% Pt@TpBpy-Cu, denoted as Pt@TpBpy-Cu.

[0074] Example 7

[0075] The method of using transition metal to tune the migration path of photogenerated charges in COFs described in Example 1 is different in that:

[0076] In step 1), 0.275 μmol of NiCl 2 Aqueous solution replaces Rh 3+ The aqueous solution was prepared as in Example 1 to obtain 0.25 wt% Pt@TpBpy-Ni, denoted as Pt@TpBpy-Ni.

[0077] Example 8

[0078] The method of using transition metal to tune the migration path of photogenerated charges in COFs described in Example 1 is different in that:

[0079] In step 1), 0.275 μmol of HAuCl 4 Aqueous solution replaces Rh 3+ The aqueous solution was prepared as in Example 1 to obtain 0.25 wt % Pt@TpBpy-Au, denoted as Pt@TpBpy-Au.

[0080] Comparative Example 1

[0081] The method of using transition metal to tune the migration path of photogenerated charges in COFs described in Example 1 is different in that:

[0082] In step 1), 0.275 umol of Rh 3+ The aqueous solution was replaced with 0.138 umol of Rh 3+ Aqueous solution, other procedures are as in Example 1.

[0083] Comparative Example 2

[0084] The method of using transition metal to tune the migration path of photogenerated charges in COFs described in Example 1 is different in that:

[0085] In step 1), 0.275 umol of Rh 3+ The aqueous solution was replaced with 0.55 umol of Rh 3+ Aqueous solution, other procedures are as in Example 1.

[0086] Comparative Example 3

[0087] Preparation of 0.25wt% Pt@TpBpy

[0088] 5.5uL containing 0.025mg of Pt 4+ H 2 PtCl6 aqueous solution and 10 mg of TpBpy were co-dispersed in 100 mL of 0.1 M ascorbic acid aqueous solution. The air was evacuated with Ar gas and the system was sealed. The photoreaction was carried out under visible light. The obtained sample was filtered, rinsed with a large amount of deionized water, and dried to obtain 0.25 wt% Pt@TpBpy, denoted as Pt@TpBpy. Its photocatalytic hydrogen evolution performance is shown in Figure 4 b.

[0089] Experimental Example 1

[0090] 1. XRD scanning was performed on 0.25wt% Pt@TpBpy-M prepared by different metal ion coordination in Example 1 and Examples 3-8. The results are shown in Figure 1 , Figure 1 It shows that the present invention successfully produced 0.25wt% Pt@TpBpy-M.

[0091] 2. The construction principle of the COF / M / Pt three-phase interface constructed using TpBpy as raw material is shown in Figure 2 shown.

[0092] 3. TEM and XPS of the 0.25wt% COF / Rh / Pt composite structure prepared in Example 1 Figure 3 As shown, the Rh-N bond in the N1s spectrum of 0.25wt% Pt@TpBpy-Rh is Figure 3 b, the valence changes of Rh and Pt are shown in Figure 3 c and Figure 3 d, indicating that the TpBpy / Rh / Pt interface was successfully constructed, and the directional transfer of photoelectrons from COF to Rh and then to Pt was promoted.

[0093] 4. Example 1 and Comparative Examples 1-2 with different concentrations of Rh 3+ The photocatalytic hydrogen evolution performance of the composite material prepared by aqueous solution coordination is shown in Figure 4 a, visible, 0.275umol Rh 3+ Aqueous solution has the best photocatalytic hydrogen evolution performance.

[0094] 0.25wt% Pt@TpBpy-M prepared by different metal ion coordination in Example 1 and Example 3-8, and compared with the traditional photo-deposited Pt nanoparticles, the photocatalytic hydrogen evolution performance is shown in Figure 4 b.

[0095] The apparent quantum efficiency of 0.25wt% Pt@TpBpy-Rh prepared in Example 1 is shown in Figure 4 c. After six cycles of testing, the photocatalyst of the present invention has no significant change in activity, indicating that it has good stability. Figure 4 d.

[0096] 5. The photocurrent and fluorescence lifetime of 0.25wt% Pt@TpBpy-Rh prepared in Example 1 are as follows: Figure 5 As shown, through Figure 5 It can be seen that the photocurrent of 0.25wt% Pt@TpBpy-Rh is enhanced and its fluorescence lifetime is prolonged, and the TpBpy-Rh of the present invention can promote electron transfer.

Claims

1. A method for tuning the photogenerated charge migration path of COFs by transition metals, comprising the following steps: 1) Coordination of transition metal ions The COFs photocatalyst is dispersed in an aqueous solution of transition metal ions, ultrasonically dispersed to make it uniformly mixed, and then stirred at room temperature for coordination adsorption. After the reaction is completed, the product is washed and purified, and the obtained solid is dried to obtain COFs coordinated with metal ions; 2) In situ photodeposition of transition metal ions The metal ion coordinated COFs are added to an ascorbic acid aqueous solution for dispersion, the air is exhausted with an inert atmosphere, the air is sealed, and the air is placed under visible light for in-situ photoreaction, and the COF-M is obtained after filtration and drying; 3) Construction of COF / M / Pt three-phase interface The prepared COF-M and H2PtCl6 aqueous solution are co-dispersed in an ascorbic acid aqueous solution, exhausted with an inert atmosphere, sealed, and placed under visible light for photoreaction. The obtained sample is filtered, rinsed with a large amount of deionized water, and dried to obtain a COF / M / Pt structured composite material Pt@COF-M, where M is a transition metal.

2. The method according to claim 1, characterized in that In step 1), the concentration of the transition metal ion aqueous solution is 200-300 mM.

3. The method according to claim 1, characterized in that The concentration of the transition metal ion aqueous solution is 260-280 mM.

4. The method according to claim 1, characterized in that In step 1), the transition metal ions are provided by RhCl3, HAuCl4, RuCl3, AgNO3, CuCl2, NiCl2 or CoCl3.

5. The method according to claim 1, characterized in that In step 1), the mass volume ratio of COFs photocatalyst to transition metal ion aqueous solution is (8-15): (4-10), unit, mg / uL, the stirring time at room temperature is 1-6h, the product is cleaned and purified by washing and filtering with deionized water, and the drying temperature is 50-100°C.

6. The method according to claim 1, characterized in that In step 2), the concentration of the ascorbic acid aqueous solution is 0.001-1M, the mass volume ratio of the metal ion coordinated COFs to the ascorbic acid aqueous solution is (8-15):(80-120), the unit is mg / mL, the inert atmosphere is Ar, the inert atmosphere treatment time is 10min-2h, and the in situ photoreaction time is 30min-2h.

7. The method according to claim 1, characterized in that In step 3), the concentration of the chloroplatinic acid aqueous solution is 10-100mM, the mass ratio of the amount of COF-M added to the H2PtCl6 in the H2PtCl6 aqueous solution is 10:(0.01-0.5), the concentration of the ascorbic acid aqueous solution is 0.001-1M, the mass volume ratio of the amount of COF-M added to the ascorbic acid aqueous solution is (8-15):(80-120), the unit is mg / mL, the inert atmosphere is Ar, the inert atmosphere treatment time is 30min-2h, the photoreaction time is 30min-2h, and the drying temperature is 50-100°C.

8. A COFs / transition metal / Pt nanoparticle composite photocatalyst, prepared by the method according to any one of claims 1 to 7.

9. Use of the COFs / transition metal / Pt nanoparticle composite photocatalyst according to claim 8 for light-driven hydrogen production.

10. The use according to claim 9, characterized in that: The specific application methods are as follows: Under light irradiation, ascorbic acid is used as a sacrificial agent and a COFs / transition metal / Pt nanoparticle composite photocatalyst is used as a catalyst to carry out light-driven hydrogen production. The concentration of the ascorbic acid sacrificial agent is 0.1-5 mol / L, the mass volume ratio of the catalyst to ascorbic acid is: (5-15):(50-200), in mg / mL, and the concentration of the ascorbic acid sacrificial agent is 0.5-2 mol / L.